2013
DOI: 10.1371/journal.pone.0081060
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Fatality among Confirmed Adult Dengue Inpatients in Singapore: A Matched Case-Control Study

Abstract: ObjectivesTo identify demographic, clinical and laboratory risk factors for death due to dengue fever in adult patients in Singapore.MethodsMulti-center retrospective study of hospitalized adult patients with confirmed dengue fever in Singapore between 1 January 2004 and 31 December 2008. Non-fatal controls were selected by matching age and year of infection with fatal cases. World Health Organization 1997, 2009 criteria were applied to define dengue hemorrhagic fever (DHF), warning signs and severe dengue. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
71
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 31 publications
(47 reference statements)
8
71
2
3
Order By: Relevance
“…In the study of thein leo et al 4% had severe hepatic impairment and 4 patients had renal impairment, maximum creatinine was 2.1 mg /dl, and 4 patients had ARDS. 13 In this study cases showed sinus braycardia in 60%, first degree heart block in 11%, and ventricular ectopics in 15% cases. While in other studies Gupta V et al showed 18% Brady cardia, 64% relative bradycardia, and 14% sinus tachycardia.…”
Section: Resultssupporting
confidence: 46%
“…In the study of thein leo et al 4% had severe hepatic impairment and 4 patients had renal impairment, maximum creatinine was 2.1 mg /dl, and 4 patients had ARDS. 13 In this study cases showed sinus braycardia in 60%, first degree heart block in 11%, and ventricular ectopics in 15% cases. While in other studies Gupta V et al showed 18% Brady cardia, 64% relative bradycardia, and 14% sinus tachycardia.…”
Section: Resultssupporting
confidence: 46%
“…However, data on comorbidities are not included in the SINAN, and can only be obtained through investigation of fatal dengue cases [33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…No observamos diferencias en cuanto a la presencia de dolor abdominal en pacientes fallecidos, cuando comparados con aquellos pacientes que no fallecieron, a diferencia de lo reportado por Thein y (15) col , quienes comparando los factores de riesgo en casos (pacientes fallecidos) y controles (pacientes no fallecidos), han demostrado que la presencia de dolor abdominal fue significativamente más frecuente en los casos que en los controles (p<0,05).…”
Section: Discussionunclassified
“…Sin embargo, Mallhi y colaboradores , describen un incremento en la estancia hospitalaria (p<0,01, OR 2.3) no así de mortalidad en los pacientes que presentaron manifestaciones hemorrágicas. Asimismo, Thein y colaboradores no demostraron una asociación de la presencia de manifestaciones (15) hemorragias con mortalidad .…”
Section: Discussionunclassified